Faktor VII-aktivierende Protease (FSAP) während der normalen Schwangerschaft - Prickartz, Isabella; Justus Liebig University Giessen (My University, 2007)
Die erste Studie zum Verhalten von FSAP in der SS ergab signifikant höhere Werte für FSAP-Antigen und Aktivität im Vergleich zur nichtschwangeren Kontrollgruppe, die Aktivitätslevel waren dabei stärker erhöht. Zudem kam es im Verlauf der Schwangerschaft zu einem signifikanten Anstieg der Werte für FSAP-Antigen und Aktivität, mit einem Maximum im 3. Trimester. Nach der Entbindung zeigte sich eine Normalisierung der Werte innerhalb von 4 Wochen postpartal. Dies ist ein ähnliches Enzymverhalten, wie das der meisten anderen Gerinnungsenzyme in der SS. Die Frequenz der Marburg I Mutation in der Studienpopulation lag mit 4.95% innerhalb der für die Kontrollgruppe ermittelten Häufigkeitsverteilung. Die schwangeren Mutationsträgerinnen zeigten ebenso wie die Kontrollgruppe eine bis zu 50% reduzierte Enzymaktivtät, bezogen auf die scu-PA-Aktivierung. Keine der 5 Mutationsträgerinnen wies eine klinisch erfasste Pathologie während der Schwangerschaft oder im Wochenbett auf. Es konnte keine Korrelation zwischen der Mutation und der Abortrate, Thromboseinzidenz oder anderen Problemen festgestellt werden.

The primary purpose of the present study was to determine the changes In FSAP in each of the trimesters of normal pregnancy and to estabilsh normal "reference values" in healthy pregnant women by comparison with a nonpregnant population. The secondary objective was to evaluate the prevalence of the Marburg I polymorphism in healthy pregnant women, a polymorphism in the FSAP gene known to exhibit reduced activity in pro-urokinase activation. Finally we performed immunostaining of FSAP to elucidate whether FSAP occurs in normal placenta.We found that both FSAP antigen and FSAP activity plasma levels markedly increase during pregnancy, attaining peak plasma levels in the 3rd trimester. After delivery, FSAP levels decline but remain above the level of non-pregnant women for several weeks in the puerperium. In the study cohort of 101 pregnants we found 5 women heterozygous for the FSAP Marbug I polymorphism. Therewith, the FSAP polymorphism carriage rate observed in pregnant women is in the range of the recently assumed frequency of 5-10% in caucasians. Pregnant Marburg I carriers were shown to exhibit a substantially diminished pro-urokinase activating potency in vitro. None of the pregnant Marburg I carriers suffered from thrombotic or other complications during pregnancy or puerperium. Nevertheless, as the small number of subjects with FSAP polymorphism remains a limitation of the present study, further epidemiological studies are required to elucidate whether female carriers of the polymorphism face a higher risk of thrombotic or other pathological events during pregnancy. As reported by other investigators, the co-segregation of the Marburg II polymorphism (found in 2 of the 101 pregnant women) had no in vitro effects on fibrinolytic activity. The physiological role of FSAP in normal pregnancy is still speculative. As an activator of plasma factor VII on the one hand, and of pro-urokinase on the other hand, FSAP might contribute to the control of the systemic hemostatic balance during pregnancy. Which of both hemostatic pathways is promoted is proposed to be regulated locally. In the present study we found FSAP present on trophoblast cells. In these cells also the urokinase type plasminogen activators are abundantly expressed. Urokinase, however, is the only protease, out of all proteases studied so far, identified to be a potential physiological acitvator of FSAP. Thus, the co-localization of FSAP and uPA in human trophoblasts provides might provide the equivalent of an autocrine loop that enhances fibrinolysis in the placenta. The high expression of FSAP observed on trophoblast cells further supports new concepts of how cogulation/fibrinolysis at the feto-maternal interface is essential for the maintenance of pregnancy. Further studies have to clarify whether the rise in FSAP is essential for the maintenance of the systemic hemostatic equilibrium in pregnant women and whether the marburg I mutation could be a riskfactor for recurrent abortion.
FSAP during normal pregnancy
Keywords: ddc:610